Molecular confirmation on the phylogenetic position of the genus Clemensiella schltr. in Marsdenieae (Apocynaceae - Asclepiadoideae) - Buera, Arleen L. (Animo Repository, 2010)
The Philippine Marsdenieae (Apocynaceae-Asclepiadoideae) comprises a total of seven genera including the imperfectly known Clemensiella Schltr. Due to its unique morphology, the position of the small genus in the tribe Marsdenieae of Asclepiadoideae was previously in question. In this first molecular study of Clemensiella, the internal transcribed spacer (ITS, nrDNA) region of three isolates were newly generated and analyzed together with previous published sequences. The present aims to assess the phylogenetic position, monophyly and closely-related genera of Clemensiella. The three Clemensiella isolates yielded a total of 630 to 642 base pairs (bp) and the average GC content ranged from 63.21% to 63.86%. Based on the strict consensus tree, the monopoly of Clemensiella is highly supported with BS = 100% and nested within the tribe Marsdenieae with BS = 61%. This study confirms the phylogenetic position of Clemensiella in Marsdenieae and its close relation to Dischidia and Hoya. Although the three Marsdenieae are distinct in their seed structures, they share common features in habit, inflorescence and corolla aestivation.